PEMBERIAN MAKANAN BAYI DAN ANAK SECARA TEPAT DALAM UPAYA PENCEGAHAN STUNTING DI DESA MAYANG, KECAMATAN GATAK - Ridwan Badhawi; Annisa Putri Amalia Setyawan; Kurnia Dea Putri Muliana; Nitiya Mahargiyani; Tasya Astrilian; Hanifah Oktaviani; Dinda Oktafiyani; Oktavian Reno Saputra; Salsabila Syiva Ajeng Pramesti; Muhammad Farhan Musyafa; Muwakhidah Muwakhidah; Sri Rahayu (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2024)
Based on the results obtained, the prevalence of stunting in Mayang Village, Gatak District is included in the high category. The incidence of stunting in Mayang Village has several causative factors, one of which is the lack of knowledge of the mother in providing proper solids according to the age of the toddler. This service aims to increase knowledge for mothers of toddlers in Mayang Village regarding how to process Infant and Child Feeding (IYCF) appropriately and according to the age of the toddler. This activity is divided into four stages, namely: (1) preparation stage, (2) implementation stage, (3) evaluation stage, and (4) program sustainability. In measuring indicators of success in this activity, a pre test and post test were carried out which were attended by 22 people. Based on the average pre-test results, a score of 80.45 was obtained and the average post-test result was 94.55. From the results obtained, it can be concluded that this activity succeeded in increasing the participants' knowledge with an average difference between the pre-test and post-test of 14.1. The advice that can be given is that the mothers of toddlers who participate in this counseling activity can practice and apply the method of processing MPASI according to the age of their children.